First report of Pythium aristosporum causing root rot on rice seedling in Taiwan - Handoko, Rose Novita Sari (Plant disease, 2022)
Rice (Oryza sativa L.) is the principle staple crops in the World and its production can be severely damaged by Pythium species. Several Pythium species including P. afertile, P. arrhenomanes, P. dissotocum, P. elongatum, P. spinosum, have been recorded to cause rice seedling root rot in Taiwan (List of Plant Diseases in Taiwan edited by Tzean et al., 2019). During the survey of rice seedling diseases, we identified a new species of Pythium that causes seedling root rot on rice in commercial nursery trays in two nursery fields in 2019 in Taichung, Taiwan. Stunting and root rot symptom were found on the affected plants and up to 20% seedlings in a nursery tray showed similar symptoms. To isolate the pathogen, symptomatic roots were surface sterilized with 75% ethanol for 1 min and rinsed in sterile water. The margin of lesion was cut off, placed on 1.5% water agar and incubated at 28 ℃. After 24 h, the hyphal tips of a white colony growing from the diseased region were transferred to potato dextrose agar (PDA) medium. Koch's postulates were fulfilled by inoculating the germinated rice seeds with mycelia. Rice seeds of O. sativa var. Tainan11 (TN11) were treated with 75% ethanol and then 1.2% NaOCl for 15 min. The sterilized seeds were soaked in sterile water under dark condition for 3 days and the water was replaced every day. Five of the pre-germinated seeds with 2~5 mm embryonic shoot were placed in a sterile petri-dish and inoculated with 3-ml mycelial suspension (OD600 = 0.045) prepared by blending the mycelia of a 3-days PDA culture using an Oster 10 speed blender 6640 (Oster, USA). The seeds-mycelia were then covered with sterilized soil mixture of Akadama soil and rice husk (1:1, volume to volume) and incubated in a growth chamber at 28 ℃. Seven days post-inoculation, the inoculated seedlings showed stunting with short and necrotic roots (Fig. S1). The pathogen was reisolated from the diseased seedlings and identified with morphology and molecular methods. For morphological characterization, the pathogen was cultured on V8 agar to produce oogonia and zoospore (Chamswarng and Cook 1985). Globose oogonia with multiple antheridia (1-5 per oogonium), inflated filamentous sporangia, vesicle with abundant zoospores, main hypha with up to 6.57 μm wide and mature aplerotic oospores with diameter 24.35-30.81 μm (average= 27.22 μm; n=20) were observed (Fig. S1) that are similar to the descriptions for P. aristosporum (van der Plaats-Niterink 1981). Genomic DNA was extracted with CTAB method (Wang and White 1997) and the sequences of the internal transcribed spacer (ITS) region and gene region of β-tubulin (tub) and cytochrome c oxidase subunit II (cox II) were amplified with published primers (Villa et al., 2006). The obtained sequences were submitted to GenBank (accession nos: OL701302 (ITS), OL763269 (tub), and OL763270 (cox II); Fig. S2). Phylogenetic relationships between this Pythium pathogen and other 55 Pythium isolates, including the type species of P. aristosporum (ATCC11101), were conducted with the concatenated sequences of tub and cox II and analyzed by Bayesian interference (Fig. S3). Based on the tree built with tub and cox II sequences, this pathogen was identified as P. aristosporum that has not been reported in rice and other plants in Taiwan. It was observed in laboratory assays that this pathogen caused significant root-rot symptoms on several major rice varieties grown in Taiwan, including TN11, Tainung67 and Kaoshiung139. It may potentially cause severe crop loss in rice production, especially in nurseries. This identification provides important information on rice disease management